Water length and height effects on the earthquake behavior of arch dam-reservoir-foundation systems - Sevim, Baris; Altunsik, Ahmet Can; Bayraktar, Alemdar; Akkose, Mehmet; Calayir, Yusuf (Korean Society of Civil Engineers-Ksce, 2011)
In this study, water length and height effects on the earthquake behavior of arch dam-reservoir-foundation systems are purposed. The study can be classified into two parts. In the first part, in order to obtain a realistic 3D arch dam-reservoir-foundation model, water length effects on the behavior of the arch dam systems are investigated. For this purpose a double curvature arch dam is modeled by forming four different water lengths related to dam Height (H) as H, 2H, 3H and 4H. Each model is analyzed in time domain and the realistic model is obtained according to the analyses results. In the second part, water height effects on the behavior of the arch dam system are investigated. The arch dam obtained from first part of the study is modeled by forming four different water heights related to dam Height (H) as 0H, 0.33H, 0.66H and H. The behavior of the dam, reservoir and foundation are expressed in terms of displacements using Lagrangian approach. The foundation is taken into account as massless; behavior of reservoir is assumed to be linearly elastic, inviscid and irrotational. In this study, all systems are modeled by ANSYS finite element program and analyses are performed using IMPVALL/I-ELC180 component of Imperial Valley (1940) earthquake. Dynamic equations of motions are solved by using Newmark integration algorithm. It is seen that both water length and height affect the earthquake behavior of the arch dams considerably.
Keywords: arch dam-reservoir-foundation system; earthquake behavior; lagrangian approach; water length and height effect